The Stabilization of Weathered Dolerite Aggregates with Cement, Lime, and Lime Fly Ash for Pavement Construction - Felix N. Okonta; Oluwapelumi O. Ojuri (Advances in Materials Science and Engineering)
An experimental program was performed on weathered dolerite specimens stabilized by adding varying percentages of cement (4, 8, 12, and 16) % and lime (6 and 12) % and a combination of lime and fly ash (6% lime + 12% Fly ash and 12% lime + 12% Fly ash) % by dry weight of soil. The strength was examined under three different curing methods, namely, membrane curing (MBC), alternate moist-air curing (MAC), and water curing (WAC), by conducting unconfined compressive strength (UCS) tests. Simple polynomial and linear functions (regression models) were used to define the relationships between the variables investigated. Membrane curing (MBC) gave results close enough to the water curing (WAC) to indicate that it can be confidently used on the field during pavement construction. From the results obtained, for class B (interurban collector and major rural roads) pavement construction, addition of 8% cement was recommended for road base construction with stabilized WDA. Also the addition of 12 + 12% Lime and Fly Ash was recommended for road subbase construction with stabilized WDA. Stabilized WDA against the prejudiced myths would perform satisfactorily for base and subbase construction in both heavily trafficked and low volume roads with economic quantities of cement, lime, and fly ash in South Africa.